1960
DOI: 10.1007/bf02644933
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification and deallergenization of castor beans

Abstract: Summary Results are reported of a series of experimental treatments of flaked castor bean meats and pomaces directed toward total detoxification of the ricin and total destruction or inactivation of the allergenic property. The treatments comprised cooking of the flaked raw meats or pomaces under various conditions of moisture and temperature, with chemicals such as sodium hydroxide, hydrochloric acid, sodium hypochlorite, formaldehyde, ammonia, ammonium sulfate, potassium permanganate, and urea, and with sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

1960
1960
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 6 publications
0
7
0
4
Order By: Relevance
“…14,15 Podemos, assim, considerar que o subproduto sólido da hidrólise ácida da torta de mamona, majoritariamente constituído por fibras e proteínas, 16 apresenta potencial emprego na composição de rações.…”
Section: Resultsunclassified
“…14,15 Podemos, assim, considerar que o subproduto sólido da hidrólise ácida da torta de mamona, majoritariamente constituído por fibras e proteínas, 16 apresenta potencial emprego na composição de rações.…”
Section: Resultsunclassified
“…As early as 1934, it was demonstrated that castor meal could be detoxified by boiling for 2 h. Since then, several methods for castor meal detoxification have been investigated. These include short but repeated boiling; autoclaving; steam heating; fermentation; ionizing radiation; mixing castor meal with the tannin‐rich meal of sal seed ( Shorea robusta Roth); and the addition of sodium hypochlorite, alkali, or acid substances (Gardner et al, 1960; Freitas, 1974; Kling, 1974; Gandhi et al, 1994; Mackinnon and Alderton, 2000). Simultaneous detoxification of both ricin and the allergens was obtained with the addition of calcium hydroxide followed by extrusion (Horton and Williams, 1989).…”
Section: Geneticsmentioning
confidence: 99%
“…The allergens in castor cause medical problems such as conjunctivitis, rhinitis and urticaria (Garcia‐Gonzalez et al., ). A sample of untreated castor meal contained 12.5% of allergen (Gardner et al., ). The allergen is more heat stable and not easily denatured unlike ricin.…”
Section: Toxins In Castor Seedmentioning
confidence: 99%